Genetic resilience to Alzheimer's disease in APOE ε4 homozygotes: A systematic review. Issue 12 (7th September 2019) - Huq, Aamira J.; Fransquet, Peter; Laws, Simon M.; Ryan, Joanne; Sebra, Robert; Masters, Colin L.; Winship, Ingrid M.; James, Paul A.; Lacaze, Paul
Abstract: Introduction: Individuals with homozygosity for the apolipoprotein E ( APOE) ε4 allele are in the highest risk category for late‐onset Alzheimer's disease (LOAD). However, some individuals in this category do not develop LOAD beyond the age of 75 years, despite being at elevated genetic risk. These "resilient" individuals may carry protective genetic factors. Methods: This study aimed to systematically review any previous studies that involved resilient APOE ε4 homozygotes and to identify possible modifying or protective genetic factors. Results: Fifteen studies met our inclusion criteria and reported genetic factors contributing to reduced risk. We found that only two single nucleotide polymorphisms, CASP7 rs10553596 and SERPINA3 rs4934‐A/A, had strong evidence. Discussion: We found a paucity of studies adequately designed to discover protective genetic factors against LOAD. Many studies combined APOE ε4 homozygotes and heterozygotes together because of small sample sizes and used control populations too young to be clearly defined as controls for LOAD.